Pengaruh Kegiatan Menggambar Teknik Graffito terhadap Kreativitas Anak Usia 5-6 Tahun di PAUD Melati Desa Sejagung Kecamatan Rantau Bayur - Bella Riswana; Indah Dwi Sartika; Mardiah Astuti; Ali Murtopo (Mathematics Education Study Program, 2025)
This research aims to analyze how garffito technique drawing activities are carried out, looking at the influence of graffito technique drawing activities on the creativity of children aged 5-6 years in PAUD Melati, Sejagung Village, Rantau Bayur District. This type of research is quantitative with a Pre-Experimental experimental research method with a One Group Pretest – Posttest design. The sample for this research was children aged 5-6 years, totaling 13 children and sampling used saturated sampling. Data collection techniques use observation, testing and documentation techniques. Data analysis techniques in this research use validity tests, reliability tests, normality tests, homogeneity tests, and t hypothesis tests. The result of tcount = 17.185 while ttable = 2.160 because tcount > ttable (17.185>2.160) then Ha is accepted and Ho is rejected. Meanwhile, the significant value is 0.001 with a significant criterion of <0.05, so it can be said that there are significant differences in children before and after receiving treatment. which means that there is a significant influence of graffito technique drawing activities on the creativity of children aged 5-6 years in PAUD Melati, Sejagung Village, Rantau Bayur District. Based on the results of research that has been carried out, the graffito drawing technique can increase children's imagination in drawing, scratching and choosing colors, children's creativity after applying the graffito technique increases and they are able to draw creatively.